Unravelling the relationship between aroma compounds and consumer acceptance: Coffee as an example. Issue 5 (7th July 2020) - Mahmud, M M Chayan; Shellie, Robert A.; Keast, Russell
Abstract: Sensory analysis is a key method to assess flavor quality and to characterize consumer preference and acceptance, whereas instrumental analysis helps to identify flavor compounds. The combination of sensory analysis and instrumental analysis provides a platform for revealing key flavor compounds associated with consumer liking. This review discusses sensory evaluation, aroma analysis, and separation techniques using coffee as a central theme where possible to explore the aforementioned techniques. Emerging statistical methodologies are discussed along with their role in tying together discrete studies to reveal important flavor compounds that are either positively or negatively associated with consumer liking. Coffee is very widely studied, a fact that may be partially ascribed to its immense popularity in modern society. To this end, more than 100 sensory lexicons have been developed and implemented to describe specific coffee characteristics and around 1, 000 volatile compounds have been identified in coffee. As a remarkably complex sample coffee has provided substantial impetus for adoption of new analytical approaches such as multidimensional separation technologies. This review describes common and emerging analytical techniques that have been employed for coffee analysis, with a particular emphasis placed on those associated with determination of volatile compounds. A comprehensive list of volatile compounds reported in coffee from 1959–2014 is included herein.